The Effectiveness of MAGIFresh Mouthwash on Halitosis in Children - Erwin, Erwin; Emini, Emini; Widiyastuti, Rini (Journal Center of Excellent : Health Assistive Technology, 2025)
Halitosis in children is a common problem that can affect their social and psychological well-being. While many interventions exist, there is a growing demand for natural and effective solutions. This study aimed to evaluate the clinical effectiveness of MAGIfresh, a novel herbal mouthwash containing Manalagi apple peel (Malus sylvestris Mill.) extract, in reducing halitosis in children. A quasi-experimental study with a one-group pretest-posttest design was conducted on 63 elementary school students. Halitosis levels were measured using a 0-5 organoleptic scale before and 30 minutes after rinsing with the mouthwash. The collected data were analyzed using the non-parametric Wilcoxon Signed-Rank Test. The results showed a statistically significant reduction in halitosis scores after the intervention (p < 0.001). The mean organoleptic score decreased from 0.74 in the pretest to 0.07 in the posttest. The findings concluded that MAGIfresh mouthwash was highly effective in reducing halitosis in children.